Besemah indigenous knowledge for forest conservation in biology education - Firsti Astari; Meilinda Meilinda; Khoiron Nazip; Nur Salwa Nisrina (Universitas Negeri Jakarta, 2026)
Indigenous knowledge plays an important role in forest conservation; however, modernization has caused indigenous knowledge almost to disappear. This study aims to determine the Besemah Indigenous Knowledge for forest conservation in Biology Education at Benawa hamlet, Penjalang Village, South Dempo District, Pagar Alam City, Indonesia. This research used a descriptive qualitative method with observation through interviews and documentation with 22 affluent information respondents. The collected data were analyzed using thematic analysis to identify patterns and meaning related to indigenous knowledge in natural resource management. Based on the results of the research, it was found that some indigenous knowledge played a role in forest conservation including the prohibition of cutting down certain trees, the prohibition of clearing land and fire sources, the prohibition of killing protected animals, the prohibition of polluting water sources, and the prohibition of entering the forest without the permission of the customary leader. The findings of this study can serve as a model of good practice in forest management, in which indeginous knowledge, customary rules, and the active role of traditional leaders guide sustainable resource use and community participation in the Ayek Mude Tebat Benawa customary forest.